No Fear: Leadership, "digital cowboys" and the "PlayStation generation" - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
Finnish entrepreneur Pekka Viljakainen would be considered as successful by most measures. At only 38 years of age, he has managed a staff of 8,000 across 20 countries from Munich. His information technology (IT) consultancy, Oy Visual Systems, had merged with Tieto, another European IT firm, and Viljakainen was made executive vice-president.